2005
DOI: 10.1016/s0004-9514(05)70038-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a water-based program on women 65 years and over: A randomised controlled trial

Abstract: The purpose of this study was to assess the effects of a water-based exercise and self-management program on balance, fear of falling, and quality of life in community-dwelling women 65 years of age or older with a diagnosis of osteopenia or osteoporosis. Fifty women with an average age of 73.3 years (range 65.5-82.4, SD 3.9) were randomised to intervention or control groups. The intervention group received a 10-week water-based exercise and self-management program compiled by Community Physiotherapy Services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
154
1
36

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(198 citation statements)
references
References 27 publications
6
154
1
36
Order By: Relevance
“…This sample composition may be seen in several other studies 10,12,15,17,18,26,27 , thereby corroborating the literature, since functional limitations occur more frequently among women, and they report suffering from a greater number of chronic conditions 28 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This sample composition may be seen in several other studies 10,12,15,17,18,26,27 , thereby corroborating the literature, since functional limitations occur more frequently among women, and they report suffering from a greater number of chronic conditions 28 .…”
Section: Discussionsupporting
confidence: 83%
“…Likewise, other studies had shown that muscle training has a positive impact on balance among older adults 8,9,11,13,18 . Our training protocol had a frequency of twice a week, for a period of six straight weeks.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Tais resultados corroboram com os dados encontrados por outros autores (10,18,19), em que o equilíbrio apresentou uma melhora significante após a execução do programa de hidroterapia avaliado pela Escala de Equilíbrio de Berg e o teste Timed Up & Go, e pelo estudo de Devereus et al (20), avaliado pelo Step test.…”
Section: Discussionunclassified
“…For example, exercising in water condition alters body movement due to increased buoyancy and increased resistance and muscle stress due to the water viscosity [11]. The water condition also provides increased safety during exercise due to reduced risk of falls and injury [12,13].…”
Section: Introductionmentioning
confidence: 99%